Sistem Pendidikan Negara Indonesia yang Tertinggal dari Negara Korea Selatan dan Perbandingan Sistem Pendidikannya - Rahmadani, Anisa; Qamaria, Elfita; Nurmaniati, Nurmaniati; Ananda, Rizki (Al-DYAS, 2023)
According to the father of Indonesian education, Ki hajar Dewantara, "Education is a conscious effort to prepare students through guidance, teaching, and / or training for their role in the future". Comparative education is analyzing two or more things to find similarities and differences. The formulation of the problem in the form of agreeing / disagreeing with the Indonesian education system is lagging behind compared to the State of South Korea? How is the education system in the State of Indonesia and the State of South Korea? What is the comparison of education between the State of Indonesia and the State of South Korea? The aim of the author is to find out that the education system in Indonesia is far behind compared to the State of South Korea, there are comparisons in the education system both curriculum, teaching methods, study time, students who are actively participating in learning lessons. In this article, the author uses a research method in the form of a descriptive method and a questionnaire method. The results of this study are that the government must be able to meet the facilities needed by students at each school, parents and educators must also be able to apply and teach children to have a high enthusiasm for learning and be able to take learning lessons.